2005
DOI: 10.1186/1471-2253-5-6
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide production from five volatile anesthetics in dry sodalime in a patient model: halothane and sevoflurane do produce carbon monoxide; temperature is a poor predictor of carbon monoxide production

Abstract: Background: Desflurane and enflurane have been reported to produce substantial amounts of carbon monoxide (CO) in desiccated sodalime. Isoflurane is said to produce less CO and sevoflurane and halothane should produce no CO at all.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Although important with desflurane, this production is insignificant with sevoflurane [15]. Environmental pollution is an essential preoccupation for anaesthesiologists using halogenated anaesthetics, and must be considered despite low sevoflurane toxicity.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
“…Although important with desflurane, this production is insignificant with sevoflurane [15]. Environmental pollution is an essential preoccupation for anaesthesiologists using halogenated anaesthetics, and must be considered despite low sevoflurane toxicity.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
“…It has been reported that CO is produced by the interaction of volatile anesthetics, including sevoflurane (12,13). We eliminated the influence of CO production through this interaction in our study, as we used intravenous anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…20 In the absence of adequate water, the carbanion decomposes and subsequently interacts with hydroxide or residual water, generating CO. 20 Sevoflurane and halothane can also generate CO, yet lack a difluoromethyl ether group, suggesting that other, less well defined mechanisms may be involved. 21 Importantly, CO production via degradation by conventional absorbents has been demonstrated with all of the volatile anesthetic agents currently in use today. 13,21,22 …”
Section: Co Exposure During General Endotracheal Anesthesiamentioning
confidence: 99%